The Effect of Perceived Security and Perceived Ease of Use on Consumers’ Behavioral Intention Mediated by Trust in Digital Payment Users - Jasmine Lamia Safira; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2026)
A crucial part of the digital financial system in developing countries comes from the use of digital payments. This study looks at what makes customers choose to use digital payment platforms, and it uses the Technology Acceptance Model (TAM) to figure this out. This model focuses on how people's beliefs about how easy a technology is to use and how useful it is influence their decision to use it. This study sent an online survey to 104 people with experience using digital payments and collected data thru this method using a quantitative approach. To check the reliability and accuracy instruments utilized in this research, the data were assessed through SPSS. Regression analysis and the PROCESS macro were used to investigate direct and indirect effects. The findings indicate that how useful people perceive digital payment systems to be is strongly influenced by how easy they find them to use, which in turn makes them more likely to use them. All questions used in this study have strong results and good reliability, with Cronbach's Alpha scores meeting standards. This result supports the effectiveness of TAM in explaining why people accept digital payments. This finding also provides useful ideas for service providers to make their systems easier to use and encourage more people to adopt digital payment technologies.